Model PBL Sebagai Upaya Meningkatkan Bernalar Kritis Materi Liturgia Fase E SMKN-1 Muara Teweh - Depide (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The purpose of the research is to improve the students’ activeness in developing their critical thinking, in the field of Catholic Education and Character in Vocational High School 1 Muara Teweh which uses Problem Based Learning. The research is done in two cycles which include the stages of planning, implementation, evaluation, and reflection. Moreover, the subject of the research is the students of phase F, grade XI with the subject of Catholic Education and Character. Then, the instruments of the research are observation sheet of students’ activities, students’ academic achievement test, and students’ questionnaires. Finally, the research shows that the implementation of Problem Based Learning can improve students’ learning activities and the result of learning in the case of Liturgia. At the end of teaching learning process, students’ activities increase 15%. Furthermore, the result of survey also shows that the students have positive feedback in implementing Problem Based Learning. Therefore, it can be concluded that Problem Based Learning is effective to be used to improve students’ learning activities and the result of learning in the subject of Catholic Education and Character.